Micropollutants Removal from Water using Microfiltration Membrane Modified with ZIF-8 Metal Organic Frameworks (MOFs) - Ragab, Doaa (2016)
A polytetrafluoroethylene (PTFE) double layer microfiltration membrane has been modified with zeolite imidazolate metal organic frameworks-8 (ZIF-8) and tested for micropollutants removal from water. The physical properties of the modified membrane and its removal characteristics are tested using progesterone as a model pollutant. Compared to the unmodified membrane, incorporation of ZIF-8 onto the polymer matrix resulted in close to 40% increase in the membrane adsorption capacity and almost doubling its water permeability which could result in significant reduction in processing specific energy consumption. The membrane maintained near 95% of its original removal efficiency after three regeneration cycles using polyethylene glycol-400. Modeling of the adsorption results agreed satisfactorily with the experimental measurements. The synergy provided by using ZIF-8 particles and the significant regeneration volume reduction ratio demonstrates the effectiveness of the approach for increasing the overall micropollutants removal capacity and allows for its further consideration for development of viable continuous membrane adsorption techniques for decontamination of water resources.